THE DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON MACROMEDIA FLASH 8 WITH CONTEXTUAL TEACHING AND LEARNING APPROACH ON PROPORTION SUBJECT - Eti Rahayuningsih; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The use of media in learning mathematics helps students understand mathematics, but learning media is still not available. This development research aims to produce an interactive learning media mathematics with contextual teaching and learning approach in the proportion of junior high school (SMP) class VII semesters. The resulting media is tested on students' feasibility and responses based on the content and objectives, instructional quality aspects, technical quality aspects, and instructional design aspects. The ADDIE development model covers five subjects: analysis, design, development, implementation, and evaluation. The instruments used are (1) assessment questionnaire by material expert, (2) questionnaire by media expert, and (3) student assessment questionnaire. This study's subjects were students of SMP Muhammadiyah 5 Yogyakarta class VIIC and students of State Junior High School (SMP Negeri) 4 Patuk class VIIB. Learning media developed in the form of CD (Compact Disk) Interactive contains SK and KD material comparison. The material on the interactive CD comes with an exercise question and evaluation question. The media is also equipped with audio, images, and navigation quickly understood and used by students. The quality of interactive learning media is seen from material experts' assessment with an average score of 3.62 or very good. While the assessment of media experts with a score of 3.71 or in the category of Very Good. In comparison, assessing the assessment by students with an average score of 3.18 or in the category of Good. The results show that the interactive learning media of mathematics with contextual teaching and learning approach the subject of proportion SMP class VII odd semester is feasible to be used in the learning process and get a positive response from the students.